Consuming Iron Biofortified Beans Increases Iron Status in Rwandan Women after 128 Days in a Randomized Controlled Feeding Trial. Issue 8 (29th June 2016) - Haas, Jere D; Luna, Sarah V; Lung'aho, Mercy G; Wenger, Michael J; Murray-Kolb, Laura E; Beebe, Stephen; Gahutu, Jean-Bosco; Egli, Ines M
Abstract: Background: Food-based strategies to reduce nutritional iron deficiency have not been universally successful. Biofortification has the potential to become a sustainable, inexpensive, and effective solution. Objective: This randomized controlled trial was conducted to determine the efficacy of iron-biofortified beans (Fe-Beans) to improve iron status in Rwandan women. Methods: A total of 195 women (aged 18–27 y) with serum ferritin <20 μg/L were randomly assigned to receive either Fe-Beans, with 86 mg Fe/kg, or standard unfortified beans (Control-Beans), with 50 mg Fe/kg, 2 times/d for 128 d in Huye, Rwanda. Iron status was assessed by hemoglobin, serum ferritin, soluble transferrin receptor (sTfR), and body iron (BI); inflammation was assessed by serum C-reactive protein (CRP) and serum α1-acid glycoprotein (AGP). Anthropometric measurements were performed at baseline and at end line. Random weekly serial sampling was used to collect blood during the middle 8 wk of the feeding trial. Mixed-effects regression analysis with repeated measurements was used to evaluate the effect of Fe-Beans compared with Control-Beans on iron biomarkers throughout the course of the study. Results: At baseline, 86% of subjects were iron-deficient (serum ferritin <15 μg/L) and 37% were anemic (hemoglobin <120 g/L). Both groups consumed an average of 336 g wet beans/d. The Fe-Beans group consumed 14.5 ± 1.6 mg Fe/d from biofortified beans, whereas the Control-Beans group consumed 8.6 ± 0.8 mg Fe/d from standard beans ( P < 0.05). Repeated-measures analyses showed significant time-by-treatment interactions for hemoglobin, log serum ferritin, and BI ( P < 0.05). The Fe-Beans group had significantly greater increases in hemoglobin (3.8 g/L), log serum ferritin (0.1 log μg/L), and BI (0.5 mg/kg) than did controls after 128 d. For every 1 g Fe consumed from beans over the 128 study days, there was a significant 4.2-g/L increase in hemoglobin ( P < 0.05). Conclusion: The consumption of iron-biofortified beans significantly improved iron status in Rwandan women. This trial was registered at clinicaltrials.gov as NCT01594359.